Strategi Manajemen Pendidikan Islam dalam Penguatan Infrastruktur, Implementasi Kurikulum Agama, dan Peningkatan Kualitas Guru di MA Baitul Makmur - Rodin, Rhoni; Harmi, Hendra; Ifnaldi, Ifnaldi; Hajja Ristianti, Dina (Media Manajemen Pendidikan, 2025)
This study aims to analyze the strategies of Islamic education management in strengthening infrastructure, implementing religious curriculum, and improving teacher quality at MA Baitul Makmur Rejang Lebong. A qualitative approach with a case study method was used. Data were collected using observation, in-depth interviews, and documentation. Data analysis employed Miles and Huberman’s interactive model. Instruments included interview guidelines, field notes, and recording devices. The study found that participatory and visionary leadership strategies contributed to infrastructure development, effective curriculum integration, and ongoing teacher development. Strong collaboration between school leaders, teachers, and the community was the key factor supporting the success of Islamic education management at the institution. Novelty/Originality of this study: This study offers a contextual model of Islamic education management by integrating infrastructure, curriculum, and human resources strategies. It contributes new insights into how Islamic schools in rural areas can advance educational quality through locally driven, value-based leadership